1988
DOI: 10.1677/joe.0.1160313
|View full text |Cite
|
Sign up to set email alerts
|

Opioid peptides do not modulate atrial natriuretic peptide or aldosterone release under basal conditions in man

Abstract: The effect of two analogues of [Met]-enkephalin, [D-Ala2,N-Phe4,Met(0)-ol5]-enkephalin and its guanyl derivative, on plasma concentrations of atrial natriuretic peptide (ANP) and serum aldosterone in six normal subjects was investigated. All subjects were given a 1 litre water load to inhibit vasopressin release. Both analogues, when injected i.v. at a dose of 100 micrograms, stimulated release of prolactin and GH and inhibited serum cortisol; there was no significant change in blood pressure, pulse rate or ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While animal studies have clearly demonstrated opioid effects on ANF release, the published data from human subjects are controversial. Clinical investigations suggest that opioids have no influence on ANF release in human subjects under basal conditions (Kidd et al, 1987;Borges et al, 1988), although Ogutman et al (1990) found significant ANF release upon morphine administration. There is evidence of a f,-endorphin effect on ANF secretion.…”
Section: Renal Effects Of a U-opioid Agonist Discussionmentioning
confidence: 99%
“…While animal studies have clearly demonstrated opioid effects on ANF release, the published data from human subjects are controversial. Clinical investigations suggest that opioids have no influence on ANF release in human subjects under basal conditions (Kidd et al, 1987;Borges et al, 1988), although Ogutman et al (1990) found significant ANF release upon morphine administration. There is evidence of a f,-endorphin effect on ANF secretion.…”
Section: Renal Effects Of a U-opioid Agonist Discussionmentioning
confidence: 99%
“…Guanyl-DAMME is a related analogue which has more recently become available, and which we have demonstrated to have a similar neuro-endocrine profile to DAMME itself (Borges, Anderson, Volta, Perry, Drury, Bloom, Besser and Grossman 1988). We confirm here that guanyl-DAMME stimulates the release of PRL, demonstrating that an endocrinologically effective dose of the compound was administered, but found no evidence of any effect on the adrenocortical response to a physiological dose of synthetic ACTH1-24 Our earlier data showing inhibition of Cortisol release following guanyl-DAMME, but no change in aldosterone (Borges et al 1988), thus appears to indicate an action which is wholly above the level of the adrenal.…”
Section: Discussionmentioning
confidence: 91%
“…This peptide has a very short biological half-life, so most of the studies on the effects of Met-enkephalin on adrenocortical function in vivo have used a long-acting analogue of the peptide, DALA. Experiments using DALA in vivo have shown a stimu¬ latory effect on aldosterone secretion when administered to rats either acutely or chronically (Robba et al 1986a), although the use of a different Met-enkephalin analogue ([D-Ala2-N-Phe4,Met(0)-ol-5]-enkephalin) did not alter aldosterone secretion in human subjects (Borges et al 1988). Some earlier studies reported that DALA has no effect on basal aldosterone production by rat zona glom¬ erulosa cells in vitro (Guaza & Borrell 1984), although another analogue (FK 33 824) stimulated aldosterone secretion by calf adrenal glomerulosa cells (Bevilacqua et al 1982).…”
Section: Zona Glomerulosa Cellsmentioning
confidence: 99%